Caracterização da fauna de morcegos (Mammalia, Chiroptera) e ocorrência de vírus rábico na região noroeste do Estado de São Paulo, Brasil - Carvalho, Cristiano de (2011)
The species richness of bat fauna and the occurrence of rabies virus were studied in urban environments from municipal districts in Araçatuba’s region and in a natural forest fragment in Valparaiso town, both located in the Northwestern Sao Paulo State. Urban samples were composed by bats, sent to UNESP Rabies Laboratory, for rabies virus research. Bats from the natural forest were collected with mist nets in four different areas selected according to accessibility characteristics and vegetation structures, usually located in possible flight routes and in areas close to water and food sources. A total of 937 samples from both areas was examined by fluorescent antibody test (FAT) and mouse inoculation test (MIT). It was identified a total of 19 species belonging to four families, Phyllostomidae, Noctilionidae, Molossidae e Vespertilionidae. In the urban area there was a predominance of insectivorous species, with greater abundance of Molossus molossus e Molossus rufus. In the forest area predominated the frugivorous species with greater abundance of Artibeus lituratus and Carollia perspicillata. The positivity rate in urban areas during the period from 2006 to 2008 was 0,75%, with seven positive cases in samples of frugivorous and/or insectivorous bats. All the bats samples from the forest area resulted negative to rabies diagnosis. This study was important to improve the knowlegment of bat diversity and rabies epidemiology in this specific region.